Sex chromosome complement contributes to sex differences in bradycardic baroreflex response - Caeiro, X. E. (2011)
To investigate whether sex chromosome complement modulates bradycardic baroreflex response and contributes to the angiotensin II– bradycardic baroreflex sex differences, we used the four core genotype mouse model in which the effect of gonadal sex and sex chromosome complement is dissociated, allowing comparisons of sexually dimorphic traits among XX and XY females, as well as in XX and XY males. In conscious gonadectomized (GDX) MF1 transgenic mice we evaluated baroreflex regulation of heart rate in response to changes in blood pressure evoked by phenylephrine (1 mg/mL), angiotensin II (100g/mL), and sodium nitroprusside (1 mg/mL). The administration of phenylephrine in GDX-XY females resulted in a significantly lower baroreflex response when compared with the other genotypes (in beats min 1mm Hg1 [slopes of regression lines for GDX-XY females 3.560.37 versus 6.060.38, 6.370.54 and 6.700.34 for GDX-XY male, GDX-XX female, and GDX-XX male mice, respectively]) {F(1,19)9.63; P0.01}. In addition, in both GDX-XY males and females, the angiotensin II-bradycardic baroreflex response was attenuated when compared with heart rate changes in GDX-XX male and female mice (in beats min1 mm Hg1 [slopes of regression lines: 2.830.28 versus 5.760.26 in GDX-XY and GDX-XX mice, respectively]) {F(1,19)13.91; P0.005}. In contrast, reflex tachycardic responses to sodium nitroprusside were comparable in all of the genotypes. These data support the hypothesis that sex chromosome complement modulates reflex inhibition of heart rate to phenylephrine and angiotensin II. Elucidating the foundational sources of sexually dimorphic traits in the regulation of baroreceptor reflex may enable the design of more appropriate sex-tailored therapeutic treatments in the future.